A Game of Women Representation Policy Implementation In District of Jember in 2014 Election - ANGIN, RIA (Jurnal Studi Pemerintahan, 2018)
The 30% quota policy is implemented by actors (political parties) and by recruiting women as legislative candidates, placing in a certain election area and number. Like a game, that effort is a political party strategy when faced with the strategy of other opposing political parties. The incumbent candidate will choose non-cooperation and move to the opposing political party if the strategy of the political party is not profitable. Instead, new candidates choose cooperatively with political parties.